Vitamin A deficiency potentiates carbon tetrachloride-induced liver fibrosis in rats - Seifert, W F; Bosma, A; Brouwer, A; Hendriks, H F; Roholl, P J; van Leeuwen, R E; van Thiel-de Ruiter, G C; Seifert-Bock, I; Knook, D L (Hepatology (Baltimore, Md.), 1994)
Earlier studies have shown that retinoid administration suppresses the generation of hepatic fibrosis and stimulates its regression in normal (i.e., vitamin A-sufficient) carbon tetrachloride-treated rats. This study focuses on the possible role of a marginal or deficient vitamin A status on carbon tetrachloride-induced fibrosis. This experimental study in rats shows that vitamin A status, reflected by hepatic retinoid content (retinol and retinyl esters), modulates the development of hepatic fibrosis induced by carbon tetrachloride. In rats with low hepatic retinoid levels (12 +/- 0.9 micrograms/gm liver), carbon tetrachloride-induced liver fibrosis was more pronounced than in rats with sufficient hepatic retinoid levels (1,065 +/- 327 micrograms/gm liver). Enhanced liver fibrogenesis was confirmed both morphologically and by a higher hydroxyproline content of the liver. It was associated with a reduced liver weight and the development of parenchymal regeneration nodules. Furthermore, carbon tetrachloride treatment itself reduced the hepatic retinoid content in rats independently of the liver vitamin A status before treatment and increased serum retinol levels in vitamin A-sufficient rats. The results show that the vitamin A status of the liver plays an important role in hepatic fibrogenesis. Low hepatic vitamin A levels, which can be the result not only of low dietary intake but also of interference with vitamin A metabolism by agents such as ethanol and carbon tetrachloride, may be a risk factor for the development of liver fibrosis. We suggest that retinoids modulate collagen synthesis and deposition irrespective of the degree of hepatocellular necrosis induced by carbon tetrachloride.